Pigment epithelium-derived factor and menopause in metastatic breast cancer - Brook, Naomi Louise (Curtin University, 2022)
This thesis investigated PEDF and menopause in metastatic breast cancer. Using immunohistochemistry and immunocytochemistry staining techniques, and cell-based functional assays, this thesis found that PEDF expression, anti-metastatic function and potential functional mechanisms are regulated by post-menopausal oestrogen levels in oestrogen receptor positive breast cancer and by pre-menopausal oestrogen levels in triple negative breast cancer. This thesis identifies two potential breast cancer patient populations who may derive greater clinical benefit from future therapeutic PEDF development.